Anthropological perspectives on CKDnt in Mexico: time for a paradigm shift on the social determinants of health - Kierans, Ciara; Padilla-Altamira, Cesar (Frontiers in Nephrology, 2023)
In Mexico, the kidneys of poor and marginalised communities are failing with little warning and no explanation. Commonly referred to as Chronic Kidney Disease of Non-traditional Origin (CKDnt), this new variant of kidney disease cannot be accounted for in conventional aetiological terms but is variously held to be a consequence of aggressive economic development, environmental degradation and precarious working and living conditions. Drawing on two interconnected ethnographic studies, and intertwining problems of cause and care, this paper will: (1) document the social conditions of disease emergence around Lake Chapala, Central Mexico and (2) follow the haphazard routes kidney patients take to access resource-intensive biotechnical treatments. It’s aim is to both challenge and re-conceptualise social determinants as social relations in order to fully account for the profoundly contextual, temporal and dynamic character of this condition as well as re-think opportunities for care and intervention.